Distinctive Features of Assessing Opportunities to Enhance the Effectiveness of Ecotourism Businesses in Regions - Hudayberganov D.; Turayev O.; Raimboyeva M.; Bobojonova D.; Kuranbayeva D.; Ruzmetov Sh. (BIO Web of Conferences)
The article examines the efficiency of ecotourism enterprises, their importance, objective necessity, features and opportunities for improvement. Based on this, the study substantiates the need to improve the efficiency of ecotourism enterprises, taking into account the current conditions of various regions. The methods of implementation and factors of influence for establishing priority areas for assessing the efficiency of ecotourism enterprises are considered. Based on various definitions of ecotourism given by economists.